2018
DOI: 10.1093/geront/gny029
|View full text |Cite
|
Sign up to set email alerts
|

Domains and Measurements of Healthy Aging in Epidemiological Studies: A Review

Abstract: This review summarizes detailed scales or methods that have been used to assess healthy aging in previous epidemiological studies. It also discusses and recommends the essential domains of healthy aging, and the relevant instruments for further epidemiological research to use in the assessment of healthy aging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
71
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(84 citation statements)
references
References 83 publications
(69 reference statements)
4
71
0
Order By: Relevance
“…From the perspective of Chinese middle-aged and elderly people in the Chong study, effective factors for positive aging include adopting a healthy lifestyle with a healthy diet and regular exercise [22]. Studies show that people who have more exercise and eat healthier are more likely to have a healthy aging [26,28]. These ndings con rm the importance of physical health promotion factors from the perspective of the middle-aged in the present study.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…From the perspective of Chinese middle-aged and elderly people in the Chong study, effective factors for positive aging include adopting a healthy lifestyle with a healthy diet and regular exercise [22]. Studies show that people who have more exercise and eat healthier are more likely to have a healthy aging [26,28]. These ndings con rm the importance of physical health promotion factors from the perspective of the middle-aged in the present study.…”
Section: Discussionsupporting
confidence: 79%
“…In order to have healthy aging, these harmful conditions must be prevented and appropriate strategies must be adopted to promote psychological health sooner, and the earlier ait is possible, the better the results will be. A review of healthy aging studies has shown that having a positive attitude is one of the characteristics of healthy aging [26]. Kindness is one of the factors that can help promote health in aging, which has been addressed in this study, and perhaps only because of the cultural fabric of Iranian society that consider kindness to be one of the highest human values.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Rowe and Kahn discussed the operational concept of successful aging that encompasses three main criteria: low risk of disease and disability, maintenance of high physical and cognitive functioning, as well as active engagement in social and productive activities [6]. In recent years, the World Health Organization (WHO) reported the concept of active aging, which is "the process of optimizing opportunities for health, participation and security in order to enhance the quality life as people age" [7]. Several empirical studies nowadays have recognized the successful aging as a "calculable gold standard of aging" [8].…”
Section: Introductionmentioning
confidence: 99%
“…Rowe and Kahn discussedthe operational concept of successful agingthat encompasses three main criteria: low risk of disease and disability, maintenance of high physical and cognitive functioning, and active engagement in social and productive activities [5]. In recent years, the World Health Organization (WHO) reported the concept of active aging, which is "the process of optimizingopportunities for health, participation and security in order toenhance the quality life as people age" [6]. Several empirical studies nowadays have recognized the successful aging as a "calculable gold standard of aging" [7].…”
Section: Introductionmentioning
confidence: 99%